Retrospective study on the effect of Body Mass Index (BMI) on maternal and neonatal outcome - Shah, Pooja M.; Chhatrapati, Anagha K.; Bandekar, Pooja K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Obesity has become health problem worldwide. Prevalence of obesity has increased globally with more incidence observed in female than male. Objective of present study was assessment of maternal outcome in term of associated medical disorder and mode of delivery and assessment of neonatal outcome. Methods: The retrospective study performed at Nowrosjee Wadia Maternity Hospital, a tertiary care centre between 1st January 2017 to 30th November 2017. Total 64 patients were enrolled. Maternal and neonatal outcomes were studied in all nulligravida women with high BMI using logistic regression adjusted for confounding variable. Results: Women with high BMI were at increased risk of hypertensive disorder of pregnancy (40.65%), diabetes (7.81%), induction of labour (62.5%), instrumental delivery (14.06%), operative intervention (42.18%), prolonged hospital stay and NICU admission (26.56%). Conclusions: This study observes increase risk of adverse outcome in pregnant women with high BMI.